Reduction in Artemisia Pollen-Specific IgE Levels During House Dust Mite Allergen Immunotherapy in Polysensitized Allergic Rhinitis Patients: A Three-Year Retrospective Study in Northern, China - Sun X; Li X; Gao T; Liu P; Liu N; Jin P; Zhi L (Journal of Asthma and Allergy)
Xiaowei Sun,1 Xu Li,2,3 Tingting Gao,4 Peize Liu,4,5 Na Liu,4 Peng Jin,6 Lili Zhi4 1Department of Otolaryngology, Jinan Children’s Hospital, Children’s Hospital Affiliated Shandong University, Jinan, 250022, People’s Republic of China; 2Department of Allergy, The First Hospital of Hohhot, Hohhot, 010030, People’s Republic of China; 3Department of Dermatology, The First Hospital of Hohhot, Hohhot, 010030, People’s Republic of China; 4Department of Allergy, Shandong Provincial Qianfoshan Hospital, Shandong Institute of Respiratory Diseases, The First Affiliated Hospital of Shandong First Medical University, Jinan, 250014, People’s Republic of China; 5Shandong First Medical University, Shandong Academy of Medical Sciences, Jinan, 250117, People’s Republic of China; 6Department of Otolaryngology, The Second Hospital of Shandong University, Jinan, 250033, People’s Republic of ChinaCorrespondence: Lili Zhi, Department of Allergy, Shandong Provincial Qianfoshan Hospital, Shandong Institute of Respiratory Diseases, The First Affiliated Hospital of Shandong First Medical University, No. 16766, Jingshi Road, Jinan, Shandong, 250014, People’s Republic of China, Email qfsyyallergy@163.com Peng Jin, Department of Otolaryngology, The Second Hospital of Shandong University, No. 247 Beiyuan Street, Tianqiao District, Jinan, Shandong, 250033, People’s Republic of China, Email jinpeng0215@126.comBackground:  Allergen immunotherapy (AIT) is a well-established treatment for allergic diseases, particularly in patients with allergic rhinitis and asthma. In regions where patients are polysensitized, AIT can have broader immunomodulatory effects. This study investigates the impact of house dust mite AIT on IgE responses to both dust mites and non-target allergens, specifically Artemisia pollen, in polysensitized allergic rhinitis patients.Methods:  This retrospective study included polysensitized patients aged 18 or older with a diagnosis of allergic rhinitis or rhinitis with asthma and positive IgE for both house dust mites and Artemisia pollen. Patients who completed at least three years of AIT for house dust mites were included. IgE levels for Dermatophagoides pteronyssinus (Der p), Dermatophagoides farinae (Der f), and Artemisia pollen were measured at baseline and after 1, 2, and 3 years of treatment. Clinical outcomes were also recorded, including Total Nasal Symptom Score (TNSS), Visual Analog Scale (VAS), and medication use.Results:  Over three years, SIgE levels for Der p significantly decreased (p = 0.0001), while Der f showed a slight and significant decrease (p = 0.0334). Artemisia pollen-specific IgE decreased modestly (p = 0.0478), despite not being the target allergen. Total IgE levels increased slightly without statistical significance (p = 0.9026). Clinical outcomes improved significantly, with reductions in TNSS, VAS, and medication scores (all p < 0.0001), alongside a decrease in eosinophil counts, reflecting clinical and immunological benefits.Conclusion:  House dust mite AIT not only reduces dust mite-specific IgE levels but also leads to unexpected reductions in IgE levels for non-target allergens, such as Artemisia pollen. This suggests that AIT has broader immunological benefits, improving overall tolerance to multiple allergens in polysensitized patients.Keywords: allergic rhinitis, allergen immunotherapy, dust mite, pollen, IgE, specific IgE, retrospective, polysensitized, treatment